Evaluasi Kepuasan Mahasiswa Terhadap Layanan Kemahasiswaan di Fakultas Sains dan Teknologi Universitas Nias Menggunakan Metode Analisis Regresi - Jurisman Waruwu; Januari Dawolo; Destriman Laoli; Yusmei Paskah Harefa; Otniel Zebua; Devi Chrisman Lase (Universitas Methodist Indonesia, 2024)
This study aimed to evaluate student satisfaction with student services at the Faculty of Science and Technology, Nias University. Involving 282 respondents consisting of 152 males and 130 females, this study used a Likert scale-based questionnaire to collect data. Validity and reliability tests showed all indicators were valid and reliable with a Cronbach's alpha value of 0.916. Satisfaction analysis was conducted through the Importance Performance Analysis (IPA) and Customer Satisfaction Index (CSI) methods, which resulted in a CSI value of 53%, indicating a good level of satisfaction although there are some aspects that need improvement. This study also identifies factors that affect student satisfaction, such as adequacy, accessibility, and quality of facilities & infrastructure, with data analysis using multiple linear regression. The results of the study are expected to provide recommendations for improving student affairs services in the future, ensuring that services remain optimal for students.